The Reality of the organizational creativity among administrators in Kuwaiti Higher Education Institution in light of contemporary global trends- A Field Study on the workers in Kuwaiti higher Education Institution\ Kuwait - - Al-Rasheedi, Fawaz Dheem (Journal of Educational and Psychological Sciences, 2020)
The study aimed at finding out the reality of the organizational creativity among administrators in Kuwaiti Higher Education Institution in light of contemporary global trends, the survey method was used, and the questionnaire was the study tool, the study sample consisting of (185) Administrative, the study results showed that the degree of appreciation and the reality of the organizational creativity among administrators in Kuwaiti Higher Education Institution in light of contemporary global trends from the standpoint of the study sample was a fair degree at an average score(3.35 From 5), the affiliation field came first, It is followed by the use of information technology, Hence strategic planning, encouraging creativity and development, The researchers recommend the need to pay attention to the creation of the creative process in higher education institutions by encouraging workers to think creatively and adopt creative ideas.
Keywords: organizational creativity; Kuwaiti Higher Education Institution; administrators; Contemporary global trends